Consonant and vowel production in the spontaneous speech productions of children with auditory brainstem implants. (2nd December 2021) - Faes, Jolien; Gillis, Steven
ABSTRACT: Auditory brainstem implantation provides hearing sensations in children and adults with anomalies of the auditory nerves. In children, perceptual benefits have been established, and research already demonstrated (limited) effects on children's speech production. The current study extends the literature by scrutinizing the phonological development of three children with ABI. Spontaneous speech samples were used to establish their phonemic inventories of vowels, word-initial consonants and word-final consonants, both independently of the target phoneme and relative to the target phoneme. The three children produced all vowels with longer device use and larger vocabulary size. Word-initial and word-final consonants appeared in the three children's spontaneous productions. However, the segmental accuracy was only moderate in the children's productions.